High spirits - Perry, Carol J. (Perry, Carol J. Haunted Haven mystery, 2022)
Greetings from Haven, Florida, a quaint, scenic old town on the Gulf Coast where Massachusetts transplant Maureen Doherty and her excessively friendly Golden retriever are the newest proprietors of the charming local inn...along with its many ghostly tenants! Now the paranormal crime investigations continue with the second installment in bestselling author Carol J. Perry's Haunted Haven Mystery Series, as Maureen is preparing for her first holiday season in her haunted century-old inn...